Inhibition of hardy kiwifruit (Actinidia aruguta) ripening by 1-methylcyclopropene during cold storage and anticancer properties of the fruit extract. (1st January 2016) - Lim, Sooyeon; Han, Seung Hyun; Kim, Jeongyun; Lee, Han Jun; Lee, Jeong Gu; Lee, Eun Jin
Highlights: Hardy kiwifruit ( Actinidia aruguta cv 'Cheongsan') shows a climacteric-like characteristic. 1-MCP delays fruit softening by reducing respiration and ethylene production at 1 ± 0.5 °C. 1-MCP down-regulates transcript levels of AcACS, AcACO, and AcLOX . Hardy kiwifruit extracts show anticancer properties against Hep3B and HeLa cells. Abstract: Hardy kiwifruits ( Actinidia arguta ) were treated with 20 μl/l 1-methylcyclopropene (1-MCP) for 16 h at 10 °C and subsequently stored at 1 ± 0.5 °C. Anticancer properties of the fruit extracts were tested against five different human cancer cells. The hardy kiwifruits, without 1-MCP treatment, showed increases in both respiration and ethylene production rates during fruit storage. The 1-MCP treatment remarkably inhibited fruit ripening by reducing respiration and ethylene production. Fruits with the 1-MCP treatment could be stored for up to 5 weeks by maintaining higher fruit firmness, ascorbic acid and total phenolic contents compared to the control. The hardy kiwifruit extracts showed anti-proliferative effects to Hep3B and HeLa cells but not to HT29, HepG2 and LoVo cells. These results suggest that the application of 1-MCP at harvest effectively delayed the ripening process of the fruits, and the fruit extract had beneficial effects for the prevention of human cancer growth.